ANALISIS RUANG TERBUKA HIJAU DALAM MENDUKUNG GREEN CITY KOTA KUPANG - Nait, Elsye K.; I. N. W. Mahayasa; Effendi, Januhari (Eternitas: Jurnal Teknik Sipil, 2023)
The provision of green open space is still an issue for some city in Indonesia, especially cities with a high population density. Green City Development Program is an effort by the central government in regional development, which refers to the principle of sustainable development in order to realize an environmentally friendly green city. Two of the eight attributes that are very important in realizing green city is a green open space and green community. Kupang city has an active area of green open space is still below 20%, indicating that the city of Kupang has not qualified in the leading green city. for that we need the effort to support the creation of a green city based on analysis of open green space Kota Kupang. Location Part II Region Development Kota Kupang were chosen for this study. This study aims to find green open space conditions today as well as implementing a design approach Green City Green Open Space and Green Community. This research uses descriptive quantitative method that aims to illustrate the need for green open space in Part II Region Development Kupang city. Based on the research, design Green Open Space actively adds 228.484 ha to 277.914 ha which was originally 49.43 Ha. In addition to the role of the community is important because of the role of the society that determines the success of a green city.